Males and females have similar neuromuscular coordination strategies of the quadriceps during fatiguing repeated all-out cycling - Cederbaum, Lauren A.; Yoon, SangHoon; Côté, Julie N. (Frontiers in Sports and Active Living, 2023)
An imbalance of vastus medialis (VM) and vastus lateralis (VL) muscle activation and patterns of dyscoordination may contribute to the sex discrepancy in the incidence of patellofemoral pain syndrome (PFPS). While some studies have examined sex-specific VM/VL coordination strategies in some tasks, no previous studies have examined sex-specific VM/VL coordination strategies during repeated sprint exercise (RSE). In this study, asymptomatic young adults (N = 39, 19 females) completed a RSE protocol consisting of 10 × 10 s all-out cycling interspersed by 30 s of passive rest. Electromyographic (EMG) signals from the VM and VL muscles were recorded throughout exercise. VM:VL ratio did not change with fatigue and was not different between the sexes. From sprint 1 to 10, VM-VL onset delay increased from 9.62 to 16.95 ms and from 19.28 to 45.09 ms in males and females, respectively (p < 0.001); however, no sex difference was found (p = 0.524). Muscle activation amplitude plateaued at different sprint repetitions in males and females while mechanical work plateaued at similar repetitions. These findings suggest that sex differences in the incidence of PFPS may not be influenced by VM/VL muscle coordination as assessed by EMG.